The role of metal sulfates in thermochemical sulfate reduction (TSR) of hydrocarbons: Insight from the yields and stable carbon isotopes of gas products - Lu, H.; Greenwood, Paul; Chen, T.; Liu, J.; Peng, P. (Pergamon, 2011)
The mechanism of thermochemical sulfate reduction (TSR) was investigated by separately heating n-C24 with three different sulfates (CaSO4, Na2SO4, MgSO4) in sealed gold tubes at 420°C and measuring the stable carbon isotope values of hydrocarbon (C1-C5) and non-hydrocarbon (CO2) products. Extensive TSR was observed with the MgSO4 reactant as reflected by increasing concentrations of H2S, 13C depleted CO2 and relatively low concentrations of H2 (compared to the control). H2S yields were already very high at the first monitoring time (12h) when the temperature had just reached 420°C, suggesting that TSR had commenced well prior to this temperature. Only trace amounts of n-C24 and secondary C3-C5 alkanes were detected at 12h, reflecting the efficient TSR utilization of the reactant and lower molecular weight alkane products. Ethane levels were still relatively high at 12h, but declined thereafter as it was subject to TSR in the absence of higher molecular weight alkanes which had already been utilized. Methane yields were consistently high throughout the 48h MgSO4 treatment. The temporal decrease in the concentrations of alkanes available for TSR may also contribute to the sharp enhancement of CO2 after 36h. Absence or dampening of the molecular and isotopic trends of MgSO4 TSR was observed with Na2SO4 and CaSO4 respectively, directly reflecting the levels of TSR reached using these sulfate treatments. For all treatments, the d13C values of C1-5 n-alkanes showed an increase with both molecular weight and treatment time. MgSO4 TSR led to a 5-10‰ increase in the d13C values of the C1-C5 hydrocarbons and a 20‰ decrease in the d13C value of CO2. The significant 13C depletion of the CO2 may be due to co-production of 13C enriched MgCO3, although this remains unproven as the d13C of MgCO3 was not measured. The difference in the d13C values of ethane and propane (?d13CEP) increased in magnitude with the degree of TSR, and this trend could be used to help evaluate the occurrence and extent of TSR in subsurface gas reservoirs. © 2011 Elsevier Ltd.